TEACHERS’ AWARENESS AND ACTUAL PRACTICES OF 21st CENTURYLEARNING AND INNOVATION SKILLS - Orak, Suheyla Demirkol; Inozu, Julıde (My University, 2021)
This research study targets to examine Turkish teachers of English language awareness, motivation, organization (institution), and actual classroom practices in terms of 21st century learning and innovation skills which are named as communication, collaboration, critical thinking, and creativity skills. For this purpose, 26 Turkish teachers of English language atFırat University School of Foreign Languages were selected as the participants. With the aim of maintain the research study, mixed method descriptive case study was conducted. In order to gather data, a questionnaire (self-report instrument) and interviews were employed. Convenience sampling was administered in the phase of participant selection. Moreover, the collected quantitative data was analysed on SPSS program version 2.00 and qualitative data was analysed with reference to interview questions. At the result session, the analyses were explained and discussed in order to be a source, and present a different point of view for the further researches. The findings of the study proved that Turkish teachers of English Language in the context of the study were in short of theoretical and conceptual knowledge regarding $21^{st}$ century learning and innovation skills, though they were excited to boost themup in the classrooms.
Keywords: Eğitim; Eğitim Araştırmaları